2022
DOI: 10.1002/wcs.1615
|View full text |Cite
|
Sign up to set email alerts
|

A tetrahedral model of autobiographical memory research design

Abstract: The field of autobiographical memory can do more to be representative of global populations experiencing and recollecting diverse events across the lifespan. To inspire such work, I present a general model for designing autobiographical memory studies. The tetrahedral model (based on Jenkins, 1979) has at its vertices context (e.g., the situated environment, activated schema, or functional goal), outcomes (e.g., the content and phenomenology of remembering), participants (e.g., the demographic characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 73 publications
2
5
0
Order By: Relevance
“…One daunting yet exciting feature of the research we reviewed above is that the canonical pattern of data on emotional differences in personal and national event cognition that is typically observed in WEIRD countries may not necessarily represent the state of affairs in other parts of the world (e.g., Choi et al, 2021; Deng et al, 2022). Much like what we have learned about memory research in laboratory settings, the pattern of data that we can expect to see emerge in studies that gauge personal and national event cognition will likely depend on characteristics of individuals, nations (or other groups that the researcher deems interesting), conditions present during encoding and retrieval, and so forth (Jenkins, 1979; see also, Talarico, 2022). For example, Mert et al (2022) recently reported a positivity bias about the national future in the United States, China, and Turkey.…”
Section: Personal and National Emotional Biases: From Daily Experienc...mentioning
confidence: 99%
“…One daunting yet exciting feature of the research we reviewed above is that the canonical pattern of data on emotional differences in personal and national event cognition that is typically observed in WEIRD countries may not necessarily represent the state of affairs in other parts of the world (e.g., Choi et al, 2021; Deng et al, 2022). Much like what we have learned about memory research in laboratory settings, the pattern of data that we can expect to see emerge in studies that gauge personal and national event cognition will likely depend on characteristics of individuals, nations (or other groups that the researcher deems interesting), conditions present during encoding and retrieval, and so forth (Jenkins, 1979; see also, Talarico, 2022). For example, Mert et al (2022) recently reported a positivity bias about the national future in the United States, China, and Turkey.…”
Section: Personal and National Emotional Biases: From Daily Experienc...mentioning
confidence: 99%
“…However, in practice, people sometimes report that they can view memories from multiple perspectives (Rice & Rubin, 2009, 2011), and there is growing interest in moving beyond this simple dichotomy (Peeters et al, 2023). Based on the tetrahedral model (Talarico, 2023), Talarico (2024) highlights how an interdisciplinary approach could be used to further understand the nature of visual perspective in context. For example, she suggests that different camera angles in film and transitions between perspectives could be applied to how visual perspective is represented in memory.…”
Section: Type Of Perspectivementioning
confidence: 99%
“…With this model, Sow et al (2023) suggest interesting experimental applications such as how research should consider that individual differences (e.g., cultural background, depression symptoms) and situational factors (e.g., potential goals to be fulfilled) may regulate the functional deployment of autobiographical memories. Other experimental avenues are proposed by Talarico (2023) who suggests a tetrahedral model of autobiographical memory research composed of context (e.g., the environment), outcomes (e.g., the content and phenomenology of remembering), participants (e.g., their demographic characteristics), and events (e.g., the lived experiences that comprise an individual's autobiography). This model can lead to promising outcomes.…”
Section: Barry Et Al (2023)mentioning
confidence: 99%